A Support System to Manage Product and Process Changes in Manufacturing. Issue 12 (2016) - Bruno, Giulia
Abstract: Different kinds of technological data are continuously generated in manufacturing enterprises, concerning the production of specific products. Especially in small enterprises, these data usually are not stored in a centralized knowledge management system. Thus, SMEs have difficulties in reusing the knowledge deriving from previous products when a new product has to be produced. Starting from the analysis of the technological data available in manufacturing enterprises, a model is designed to support the structuring of the manufacturing knowledge. It was also provided a classification of the possible changes in the manufacturing process that can be seen as variation to a previous product and thus can be managed more efficiently. In fact, changes in the components or in the production operations can be done more easily starting from the knowledge of a previous product instead of redoing from scratch. The usage of the proposed management system will allow a more easy evaluation of different product and process alternatives from the point of view of the final cost.